The world through the eyes of angels - Saʻīd, Maḥmūd, 1938- (Middle East literature in translation., 2011)
Mosul, Iraq, in the 1940s is a teeming, multiethnic city where Arabs, Kurds, Assyrians, Jews, Aramaeans, Turkmens, Yazidis, and Syriacs mingle in the ancient souks and alleyways. In these crowded streets, among rich and poor, educated and illiterate, pious and unbelieving, a boy is growing up. Burdened with chores from an early age, and afflicted with an older brother who persecutes him with mindless sadism, the child finds happiness only in stolen moments with his beloved older sister and with friends in the streets. Closest to his heart are three girls, encountered by chance: a Muslim, a Christian, and a Jew. After enriching the boy's life immensely, all three meet tragic fates, leaving a wound in his heart that will not heal. A richly textured portrayal of Iraqi society before the upheavals of the late twentieth century, Saeed's novel depicts a sensitive and loving child assailed by the cruelty of life. Sometimes defeated but never surrendering, he is sustained by his city and its people.